Barriers and facilitators associated with the use of mental health services among immigrant students in high-income countries: A systematic scoping review. - Christelle Dombou; Olumuyiwa Omonaiye; Sarah Fraser; Jude Mary Cénat; Karine Fournier; Sanni Yaya; Sanni Yaya (PLoS ONE)
Background Immigrant students face various challenges in high-income countries that can contribute to the decline of their mental well-being upon arrival in their host country. Despite the growing population of these students in several high-income countries, there is inadequate attention given to their mental health needs and their access to mental health services. Thus, this systematic scoping review aimed to identify gaps in existing research relating to the barriers and facilitators associated with access to and use of mental health services in high-income countries. Methods Following the PRISMA-ScR checklist as guidance we systematically searched Ovid Medline, APA PsycInfo, Education Source, CINAHL, Web of Science databases for peer reviewed articles related to barriers and facilitators of mental health service use among immigrant students. We conducted a narrative evidence synthesis to highlight barriers and facilitators to the use of mental health services. Results Out of the 2407 articles initially found, 47 studies met the inclusion criteria and were considered for this review. The increasing attention towards the mental health concerns of immigrant students and their access to mental health services is evident. However, various barriers like stigma, insufficient knowledge, or adherence to traditional gender roles (such as masculinity) hinder their utilization of these services. On the other hand, factors such as being a woman, having a strong sense of cultural adaptation, or possessing adequate mental health literacy serve as facilitators for accessing mental health services. Conclusion These students have unique experiences, and their needs are often unmet. To improve their mental health and use of mental health services, it is important to consider the barriers they face and their unique experience in their specific life context and to develop tailored prevention and intervention programs.